On applications of coupled fixed point theorem in hybrid differential equations of arbitrary order - Muhammad Shaob; Kamal Shah; Rahmat Ali Khan (Matrix Science Mathematic, 2017)
In this manuscript, we use fixed point theorem due to Bashiri theory and develop sufficient conditions for existence of solution of coupled system of fractional differential equation in Banach space.